(untitled) (Crimson Journal of Science and Technology, 2025)
Introduction: Access to safe drinking water is a critical public health concern in Nepal, where both rural and urban communities face challenges in water quality and distribution. In rural areas like Kalari, Chautara, natural water sources are often impacted by pollution from human and livestock activities, while in urban areas such as Dhalpa-5, Kritipur, rapid urbanization and aging infrastructure contribute to water scarcity and potential contamination. Limited access to safe water increases the risk of waterborne diseases, with contaminants like bacteria, pathogens, and sediments affecting community health. Despite government initiatives and localized efforts to provide clean drinking water, infrastructural constraints and environmental challenges persist. This study provides a comparative assessment of the drinking water conditions in Kalari and Dhalpa, focusing on water source reliability, distribution frequency, treatment practices, and health impacts on the local population. Methods: A mixed-method approach was used, incorporating both quantitative and qualitative data collection. Surveys and interviews were conducted with 35 households from each area to assess water source, consumption patterns, and satisfaction levels. Secondary data from governmental reports supplemented the findings. Results: In Kalari, most households receive water twice daily from government or community sources, whereas Dhalpa relies on government supply with limited distribution, sometimes supplemented by bottled or tanker water. A higher percentage of residents in Kalari use untreated tap water directly, whereas more Dhalpa residents use filtration methods. Health concerns were slightly higher in Dhalpa, with a few respondents reporting mild gastrointestinal issues from unfiltered tap water. Conclusion: While both areas benefit from drinking water facilities, water security is limited by supply frequency and infrastructure. The study highlights the need for regular water treatment and increased awareness on safe water handling to reduce health risks.